Pendampingan Kelompok Sadar Wisata Pantai Tlangoh Menuju “Blue Marine Economy” Berbasis Pariwisata Halal - Muhammad Anas; Fauzie Senoaji; Gusmaniarti Gusmaniarti (Journal of Community Development, 2025)
The background of the community service (PKM) with the following problems; Firstly, towards the "Blue Marine Economy", the Tlangoh Beach area still does not meet the standards of business activities, especially in the availability of supporting facilities, it can be seen that there is still a lot of scattered garbage, lack of clean water availability, limited toilet facilities, poor mushola management standards and poor sewage management, Secondly, in terms of halal tourism, the Tlangoh Beach area still does not have a digital-based financial management system to support halal tourism activities, and thirdly, in terms of halal tourism, food and beverage products managed by MSMEs at Tlangoh Beach still do not meet halal certification standards. The purpose of the PkM activity is to empower the community, especially the POKDARWIS, to develop a tourism village by improving the welfare of the village community through creating jobs and increasing the village's original income. PKM activities are carried out in 5 stages, namely Preparation Stage, preparing all the needs required for the implementation of activities, Implementation Stage, including training and assistance in the form of increasing knowledge, simple bookkeeping skills, halal product certificates, and renovation of mushollahs, Monitoring and Evaluation Stage, Partner Participation, POKDARWIS plays an active role as a participant in training and mentoring activities, provides the required formal documents, and provides consumption as much as possible, and Evaluation and Follow-up, in two forms, namely: Activity-based evaluation there is an increase in knowledge by 53%, and evaluation of usefulness in the form of use of Mushollah renovations by visitors.